Head to head comparison of adverse effects and efficacy between high dose deflazacort and high dose prednisolone in systemic lupus erythematosus: a prospective cohort study. (May 2018) - Ganapati, A; Ravindran, R; David, T; Yadav, B; Jeyaseelan, V; Jeyaseelan, L; Danda, D
Background: Deflazacort (DFZ), an oxazoline derivative of prednisolone (PDN), has a dose equivalence of 1.2:1 (mg) to PDN. No study to date has compared adverse effects and efficacy of high doses of DFZ as against high-dose PDN in systemic lupus erythematosus (SLE). Objectives: To compare adverse effects of high dose DFZ and PDN in SLE patients, especially in terms of cushingoid features and gain in body weight, 3 and 6 months after initiation of these agents. Methods: In both the steroid arms, the following outcome parameters were assessed at 3 and 6 months: (a) cushingoid features by Cushing's Severity Index (CSI) (b) hirsutism by modified Ferriman Gallwey score (c) weight gain by difference (Δ, delta) of weight (in kilograms). Results: Patients on PDN had 1.6 kg (3.2%) and 2 kg (5.1%) higher median weight gain as compared to those on DFZ at 3 and 6 months respectively ( p = 0.012 and 0.001). PDN caused 10% and 22.2% higher increment in median hirsutism scores as compared to DFZ at 3 months and 6 months follow-up, respectively ( p = 0.004 and 0.002). PDN caused 100% higher increase in median CSI scores than DFZ at 6 months ( p = 0.03). There was no significant difference by generalized estimation equation between the groups with respect to changes in SLEDAI, renal SLEDAI, anti-dsDNA titres and C3/C4 levels. There were two serious infections (requiring hospitalization/intravenous antibiotics) in the PDN group, while none in the DFZ group. Conclusion: Comparable intake and tapering of high dose DFZ and PDN in active SLE revealed 2-fold less weight gain, 2.5-fold less hirsutism and 1.5-fold lower cushingoid severity index as well as lower glycaemic elevation in the DFZ group as compared to PDN group. Both had similar efficacy.